Assessment and Interpretation of Vitamin and Trace Element Status in Sick Children: A Position Paper From the European Society for Paediatric Gastroenterology Hepatology, and Nutrition Committee on Nutrition. Issue 6 (June 2020) - Gerasimidis, Konstantinos; Bronsky, Jiri; Catchpole, Anthony; Embleton, Nicholas; Fewtrell, Mary; Hojsak, Iva; Indrio, Flavia; Hulst, Jessie; Köglmeier, Jutta; de Koning, Barbara; Lapillonne, Alexandre; Molgaard, Christian; et al.
Abstract : ABSTRACT: Assessment of vitamin and trace element status (VTE) is important in the clinical management of the sick child. In this position paper, we present the various assessment methods available to the clinical practitioner, and critically discuss pitfalls with interpretation of their results. There are 4 main approaches to assess the VTE body status of an individual patient including clinical examination, dietary assessment, and measurement of direct and indirect biomarkers of VTE in biological samples. Clinical signs of VTE deficiencies usually present only when body stores are substantially depleted and are often difficult to detect or differentiate from other nonnutrient-related causes. In isolation, dietary assessment of micronutrients can be inaccurate and imprecise, in disease and in individual patient assessment but may be useful to complement findings from other VTE assessment methods. Use of biomarkers is the most common approach to assess VTE status in routine practice but in the presence of systemic inflammatory response and in the absence of appropriate paediatric reference intervals, interpretation of biomarker results might be challenging and potentially mislead clinical practice. The use of a multimodal approach, including clinical examination, dietary assessment, and laboratory biomarkers is proposed as the optimal way to ascertain the VTE status of individual patients. In the presence of acute inflammatory conditions, VTE measurements in plasma should be replaced by biomarkers not affected by systemic inflammatory response or delayed until inflammatory state is resolved.